Postsurgical rehabilitation for adults with low back pain with or without radiculopathy who were treated surgically: protocol for a mixed studies systematic review - Ginny Brunton; Silvano Mior; Carol Cancelliere; Jessica J. Wong; Hainan Yu; Margareta Nordin; Paulo Pereira; Heather Shearer; Gaelan Connell; Leslie Verville; Anne Taylor-Vaisey (BMJ Open)
Introduction Surgical rates for low back pain (LBP) have been increasing in Europe, North America and Asia. Many patients treated surgically will require postsurgical rehabilitation. Little is known about the effectiveness of postsurgical rehabilitation interventions on health outcomes or about patients’ experiences with these interventions.Objectives To conduct a mixed studies systematic review of quantitative and qualitative studies regarding: (1) the effectiveness and safety of postsurgical rehabilitation interventions for adults with LBP treated surgically and (2) the experiences of patients, healthcare providers, caregivers or others involved with the rehabilitation.Methods and analysis We will search MEDLINE, Embase, PsycINFO, CINAHL, the Index to Chiropractic Literature, the Cochrane Controlled Register of Trials and the Rehabilitation & Sports Medicine Source for peer-reviewed empirical studies published from inception in any language. Studies using quantitative, qualitative and mixed methodologies will be included. We will also search reference lists of all eligible articles. Data extraction will include type of presurgical pathology, indication for surgery, surgical procedure, how the intervention was delivered and by whom, context and setting. We will conduct a quality assessment of each study and consider study quality in our evidence synthesis. We will use a sequential approach at the review level to synthesise and integrate data. First, we will synthesise the quantitative and qualitative studies independently, conducting a meta-analysis of the quantitative studies if appropriate and thematic synthesis of the qualitative studies. Then, we will integrate the quantitative and qualitative evidence by juxtaposing the findings in a matrix.Ethics and dissemination Ethical approval is not required for this knowledge synthesis. Findings will be disseminated through knowledge translation activities including: (1) presentations at national and international conferences and scientific meetings; (2) presentations to local and international stakeholders; (3) publications in peer-reviewed journals and (4) posts on organisational websites.PROSPERO registration number CRD42019134607.